Importance of Fire Prevention and Fire Safety Education among Barangay Officials of Candaba Pampanga - Arrozal, Mark Amiel; de Asis, Ferdinand; de Asis, Romae; Hernaez, Maria Krisia Fae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the importance of fire prevention and fire safety education among barangay officials in Candaba, Pampanga, with emphasis on community preparedness, governance, and disaster risk reduction. Anchored on the Knowledge, Attitude, and Practice (KAP) Theory, Cause and Effect Theory, Cognitive Flexibility Theory, Social Learning Theory, and Protection Motivation Theory, the study utilized a descriptive research design to systematically assess perceptions regarding fire prevention and fire safety activities. The respondents consisted of 264 barangay officials from the 33 barangays of Candaba, Pampanga, selected through total population sampling. Data were gathered using a validated survey questionnaire employing a four-point Likert scale and analyzed using frequency count and weighted mean. Findings revealed that fire prevention practices, house-to-house fire safety engagement, fire safety lectures and seminars, and drills and simulations were generally perceived as Somewhat Important. Barangay officials highly valued technical and structured interventions such as electrical safety measures, professional conduct during house-to-house engagement, community-based fire safety lectures, and drills in high-risk areas. However, regular implementation, follow-up actions, monitoring systems, and continuous participation were not fully prioritized, indicating a gap between awareness and actual practice. The study concluded that strengthening fire safety requires a systematic and multi-level approach integrating education, participation, drills, policy support, and collaboration with the Bureau of Fire Protection. Recommendations included regular seminars, customized lectures, annual drills, policy integration, and strengthened monitoring mechanisms to improve institutionalized fire safety practices. The study supports Sustainable Development Goal 3 on Good Health and Well-Being, Sustainable Development Goal 11 on Sustainable Cities and Communities, Sustainable Development Goal 16 on Peace, Justice, and Strong Institutions, and Sustainable Development Goal 17 on Partnerships for the Goals through the promotion of community safety, disaster preparedness, local governance, and institutional collaboration. The study contributes to sustainability by strengthening community resilience, improving public safety awareness, and supporting long-term fire prevention and disaster preparedness initiatives at the barangay level.
Keywords: Barangay Officials; Community Preparedness; Disaster Risk Reduction; Fire Prevention; Fire Safety Education; Governance; Sustainable Development